Creating sustainable supply chain through green procurement: a case of Tenaga Nasional Berhad (TNB) / Suhaili Salim - Salim, Suhaili (Faculty of Business and Management, 2012)
This study focuses on creating sustainable supply chain through green procurement. The aims of this study are to identify the relationship between regulations, customer pressures, social responsibility and expected business benefits with green procurement adoption, to determine if there is any difference in terms of green procurement adoption among Stesen Janaelektrik Sultan Ismail (SJSI) Paka, Stesen Janaelektrik Sultan Azlan Shah (SJAS) Manjung, Stesen Janakuasa Kapar (SJK) and Stesen Janaelektrik Sultan Iskandar Shah (SJSIS) Pasir Gudang, to discover the strength of predictors in explaining the variance in green procurement adoption and to identify the significant predictor(s) that influence(s) the green procurement adoption. A questionnaire was the instrument used in getting the data with 50 samples from each station. The Correlation of coefficient was adapted and for this exploratory study, it was found that all identified independent variables have significant relationship with green procurement adoption. Apart from that, there is a difference in terms of green procurement adoption between SJSI Paka and SJK Kapar. Whilst the strength of predictors in explaining the variance in green procurement adoption is 59.3%. Of the four variables, customer pressures were found to be the strongest predictor of the adoption of green procurement. This was followed by regulations, social responsibility and expected business benefits. With increasing awareness of environmental protection worldwide, the green trend towards conserving the Earth’s resources and protecting the environment is overwhelming, exerting pressure on corporations in Thailand. The pressure accompanying globalization has prompted enterprises to improve their environmental performance (Zhu and Sarkis 2006)